Pemanfaatan Sari Pati Buah Sukun (Artocarpus altilis) Sebagai Alternatif Media Pertumbuhan Aspergillus niger - Tuty Yuniarty; Anita Rosanty (Biogenesis: Jurnal Ilmiah Biologi, 2017)
Aspergillus niger is a fungi family Trichocomaceae that form filaments, mycelia, and conidiospore can produce citric acid and does not contain mycotoxins. The media are used as a medium for growth of the fungi Aspergillus niger is SDA (Saboroud Dextrose Agar) which commercially available. This study aims to determine the possible use of based starch breadfruit as alternate media for Aspergillus niger. Inoculation of the fungi Aspergillus niger was conducted using a single dot (one point). The results found macroscopic colonies dark brown to black, round and microscopic hyphae and spores use KOH 10% solution that is suggesting that Aspergillus niger can grow in the growth media made from starch breadfruit.